New landscape design - Holden, Robert (New York Architectural Press, 2003)
In addition, the book provides the reader with insight into many of the other concerns facing landscape architects, such as the image and the function of urban spaces, ecological survival, sustainability, native people and their settlements, environmental education and the role and nature of human settlement.
Keywords: LANDSCAPE ARCHITECTURE (AR-LA)